1984
DOI: 10.1002/j.1460-2075.1984.tb01934.x
|View full text |Cite
|
Sign up to set email alerts
|

The molecular basis for the differential translation of TMV RNA in tobacco protoplasts and wheat germ extracts

Abstract: Translation of tobacco mosaic virus (TMV) RNA in tobacco protoplasts yields the 17.5‐K coat protein, a 126‐K protein and a 183‐K protein which is generated by an efficient readthrough over the UAG termination codon at the end of the 126‐K cistron. In wheat germ extracts, however, only the 5′‐proximal 126‐K cistron is translated whereas the 183‐K readthrough protein is not synthesized. Purification and sequence analysis of the endogenous tyrosine tRNAs revealed that the uninfected tobacco plant contains two tRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(64 citation statements)
references
References 43 publications
4
60
0
Order By: Relevance
“…The foregoing observations are consistent with a translation strategy for BNYVV RNA-2 involving partial readthrough of the termination codon of the viral coat protein cistron to produce P85, Beier et al (1984) have recently isolated and characterized two closely similar tRNA tyr species from tobacco which can further stimulate readthrough of the tobacco mosaic virus (TMV) 126K amber termination codon. We have found that the tobacco suppressor tRNA tyr has a similar effect on translation of BNYVV RNA-2.…”
Section: Amber Suppressor Trna Enhances Readthrough O F the Bnyvv Coasupporting
confidence: 70%
“…The foregoing observations are consistent with a translation strategy for BNYVV RNA-2 involving partial readthrough of the termination codon of the viral coat protein cistron to produce P85, Beier et al (1984) have recently isolated and characterized two closely similar tRNA tyr species from tobacco which can further stimulate readthrough of the tobacco mosaic virus (TMV) 126K amber termination codon. We have found that the tobacco suppressor tRNA tyr has a similar effect on translation of BNYVV RNA-2.…”
Section: Amber Suppressor Trna Enhances Readthrough O F the Bnyvv Coasupporting
confidence: 70%
“…This observation suggests that the presence of the Q modification in the wobble position of the anticodon restricts recognition of the tRNA to the cognate UAC and UAU Tyr codons whereas the presence of an unmodified G permits the additional recognition of UAG. A correlation between suppression activity and undermodification in the wobble position was also observed in wheat germ [23] and lupin tRNAs [24].…”
Section: Nonsense Suppression Via Misreadingmentioning
confidence: 55%
“…It has been proposed [23] that the G of the anticodon could adopt a 'syn' conformation that would allow it to hydrogen bond with the G of the codon. On the contrary, the presence of a bulky side chain which projects out of the Q!PA anticodon loop [25], would prevent by steric hindrance the Q nucleoside from adopting such a conformation.…”
Section: Nonsense Suppression Via Misreadingmentioning
confidence: 99%
“…The 0.5 kb EcoRI fragment of pTtY5 was completely sequenced. A comparison with the two major cytoplasmic tRNA Ty~ isoacceptors from wheat [26] reveals that four of the nine sequenced Triticum tRNA Ty~ genes code for tRNA~ yr, whereas two code for tRNAff y~ (Fig. 2).…”
Section: Isolation and Nucleotide Sequences Of Six Trna Tyr Genesmentioning
confidence: 99%